The Effect of Earned Versus House Money on Price Bubble Formation in Experimental Asset Markets. (18th August 2014) - Corgnet, Brice; Hernán-González, Roberto; Kujal, Praveen; Porter, David
Abstract: Does house money exacerbate price bubbles? We compare house money asset market experiments with an earned money treatment where initial portfolios are constructed from a real effort task. Bubbles occur; however, trading volumes and earnings dispersion are significantly higher with house money. We investigate the role of cognitive ability in accounting for the differences in earnings distribution across treatments by using the cognitive reflection test (CRT). Low CRT subjects earned less than high CRT subjects. Low CRT subjects were net purchasers (sellers) of shares when the price was above (below) fundamental value. The opposite was true for high CRT subjects.